Gennady Kharlampievich Gruntovsky - «SISJP NAMS Ukraine», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article deals with the 75th anniversary of the birthday of a famous scientist in the field of orthopaedics and traumatology, chief scientist of Sytenko Institute of Spine and Joint Pathology of the National Academy of Medical Sciences of Ukraine, winner of the State Prize of Ukraine in the field of science and engineering, Professor Gruntovsky G. K.